Spotlight on cabozantinib for previously untreated advanced renal cell carcinoma: evidence to date - Bersanelli, Melissa (Cancer Manag Res, 2018)
BACKGROUND: In the past few years, new drugs made their appearance in the first-line setting of treatment for metastatic renal cell carcinoma (mRCC), and cabozantinib is one among them. The present systematic review aims to point out any evidence published to date about first-line treatment with cabozantinib for mRCC patients, describing their outcome in all end points explored by the literature. METHODS: PRISMA guidelines were followed. A systematic assessment of literature and peer- reviewed presentations was performed by searching PubMed and major oncology meeting resources, from the database inception until June 25, 2018. The following keywords were used: “cabozantinib or cabozantinib-s-malate or XL184” and “renal cell carcinoma or kidney cancer or clear cell renal carcinoma or renal cancer” and “first-line or untreated or treatment-naïve or primary treatment”. All types of original clinical studies were included, evaluating either cabozantinib monotherapy or any systemic drug combination containing cabozantinib for previously untreated patients with mRCC. RESULTS: From potential 75 titles and abstracts, seven publications were selected. One was the main report of a randomized clinical trial (the CABOSUN study); four papers reported updated results, secondary or subgroup analyses from the same study population; and further two reports consisted of network meta-analyses. From the additional search for ongoing clinical trials, six studies currently in progress were reported. CONCLUSION: According to the reported evidence, cabozantinib may be a viable first-line option in mRCC patients with intermediate or poor risk according to International Metastatic Renal Cell Carcinoma Database Consortium model. It offers an undoubtful advantage in terms of progression-free survival, despite quite high rates of G3–4 toxicity, modest objective response rate, and no survival advantage. Nevertheless, given the availability of an immunotherapy combination that significantly improved overall survival for the same population in a Phase III trial and the indisputable efficacy of cabozantinib as second-line treatment, this drug may be devoted as a rescue option in patients progressive to primary therapy.